2016
DOI: 10.1089/zeb.2015.1159
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Social Behavior in the Wild

Abstract: Wild zebrafish exhibit a wide range of behavior. We found abundant wild zebrafish in flowing rivers and still water, in large, tightly-knit groups of hundreds of individuals, as well as in small, loose shoals. In two still-water populations, zebrafish were quite small in body size, common, and in tight groups of up to 22 fish. As in earlier laboratory studies, these zebrafish exhibited very low levels of aggression. In slowly flowing water in central India, zebrafish were relatively rare and gathered in small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
132
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(147 citation statements)
references
References 57 publications
9
132
0
Order By: Relevance
“…Shoaling is a robust social behavior typical of zebrafish that is readily observable in the wild (Spence et al, 2008;Suriyampola et al, 2016) and easily elicited in a laboratory setting by providing suitable social stimuli (Qin et al, 2014). For example, the existence or strength of shoaling may be tested using a choice task in which the test fish is placed singly in the middle of an aquarium flanked on opposite sides by social or control stimuli (Miller and Gerlai, 2007).…”
Section: How To Induce and Measure Shoaling In Zebrafishmentioning
confidence: 99%
See 1 more Smart Citation
“…Shoaling is a robust social behavior typical of zebrafish that is readily observable in the wild (Spence et al, 2008;Suriyampola et al, 2016) and easily elicited in a laboratory setting by providing suitable social stimuli (Qin et al, 2014). For example, the existence or strength of shoaling may be tested using a choice task in which the test fish is placed singly in the middle of an aquarium flanked on opposite sides by social or control stimuli (Miller and Gerlai, 2007).…”
Section: How To Induce and Measure Shoaling In Zebrafishmentioning
confidence: 99%
“…Abiotic factors such as substrate of home/testing tanks, speed of water flow, and presence of vegetation can affect social interaction, particularly aggressive and reproductive behaviors (Keck et al, 2015;Suriyampola et al, 2016).…”
Section: The Effect Of Environmental Stimuli On Shoalingmentioning
confidence: 99%
“…The most frequently studied school properties include cohesion, which is usually indicated by the nearest neighbor distance (NND), and coordination, which is indicated by the synchronization of swimming activity and the polarity of orientation within the school. It has been found that the ecological benefits and costs of group behavior associated with a specific property of the school varies with species and group size (Gimeno et al 2016, Suriyampola et al 2016a) Investigation in fish species also found that water flow showed a profound effect on school properties such as cohesion (Suriyampola et al 2016b) and polarization (Chicoli et al 2014). Thus, further investigation on whether group size has different effects on school traits among fish species that prefer different flow regimes may yield interesting results.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…Detailed description of this repertoire is beyond the scope of this review, but briefly, zebrafish have an elaborate courtship display/spawning behaviour, show transient territoriality, exhibit numerous agonistic behaviours, and most importantly shoal, the focus of the current review (Darrow & Harris, 2004;Miller & Gerlai, 2007Spence et al, 2008;Suriyampola et al, 2016;Teles & Oliveira, 2016). Shoaling is a form of group forming, or aggregation behaviour, in which subjects stay in close proximity to each other.…”
Section: Zebrafish Social Behaviourmentioning
confidence: 99%